ANALISIS TINGKAT PEMAHAMAN MASYARAKAT TERHADAP PELAKSANAAN ZAKAT PERTANIAN DI DESA NGALI KECAMATAN BELO KABUPATEN BIMA - samusiah, samusiah; Fathurrahman, Fathurrahman; Katman, Muhammad Nasri (Investama : Jurnal Ekonomi dan Bisnis, 2024)
The background of this research is that zakat is a pillar of Islam that must be carried out when the nisab and haul have arrived. Agricultural zakat is one of the obligatory zakat to be issued at harvest time and the nisab is the same as rice. Understanding is the ability to explain and interpret something, this study aims to determine the level of understanding of the people in Ngali Village, Belo District, Bima Regency regarding agricultural zakat. The formulation of the problem in this research is. How is the level of understanding of the people in Ngali Village, Belo District, Bima Regency towards agricultural zakat. The subjects of this research were the people of Ngali Village, Belo District, Bima Regency, while the subjects in this study were the people's understanding of agricultural zakat in Ngali Village, Belo District, Bima Regency. The type of research used is the type of field. The data sources used are prime and secondary data. While the data collection techniques are observation, questionnaires and documentation, to analyze the data using descriptive qualitative methods. The number of population in this study was 229 people using the slovin formula, based on the results of the research which showed through the answers of the respondents it could be concluded, an analysis of people's understanding of agricultural zakat in the village of Ngali, Belo sub-district, Bima district, answered "good" about agricultural zakat with a percentage of 64.70%, socialization is needed to the community so that people understand agricultural zakat.